Combined effects of oxandrolone and exercise on muscle recovery in rats with severe burn and hindlimb unloading - Palackic, Alen; El Ayadi, Amina; Wade, Charles E.; Baer, Lisa A.; Branski, Ludwik K.; Hundeshagen, Gabriel; Kleinhapl, Julia; Wolf, Steven E.; Song, Juquan (Shock, 2025)
Background: Loss of muscle mass and strength in patients who have experienced severe burns is dramatic and associated with subsequent functional impairment. Past work has shown that exercise and oxandrolone, an anabolic steroid, individually improve muscle function and muscle mass in severely burned patients. This study aims to evaluate the effect of oxandrolone treatment combined with resistance exercise on muscle atrophy and investigate the protein synthesis and mitochondrial biogenesis pathways in a hindlimb suspension model. Methods: Twenty-four Sprague-Dawley rats received 40% total body surface area (%TBSA) scald burns and were then placed for hindlimb unloading. All animals were randomly grouped into vehicle (corn oil) without exercise (V/NEX), oxandrolone administration (0.1 mg/kg/d) without exercise (OX/NEX), vehicle with exercise (V/EX), or oxandrolone with exercise (OX/EX) (n = 6/group). On day 14, isometric forces of the left plantaris and soleus muscle were measured by using a muscle lever system with dynamic muscle control and analysis software. Fatigue measurement was only performed in the soleus muscle. The tissue of the muscle was then collected for protein extraction. Western blots were performed to study signal alternations and mitochondrial biogenesis pathways. Results: Tetanic force (Po) was significantly increased in the plantaris with exercise rather than with oxandrolone treatment. Fatigue index (FI) was lower, and integration was significantly elevated in the soleus with exercise but not with oxandrolone treatment. Fatigue curve in the soleus further revealed that the average maximum force was achieved in soleus with either oxandrolone treatment or exercise alone independently. Raptor and p-Akt levels are elevated in the OX/EX group, whereas PGC1a expression was not altered. Conclusion: Oxandrolone and resistance exercise have independent positive effects on muscle function recovery in this clinically relevant rodent model of severe burn. Both treatments combined increased signaling pathways by increasing protein synthesis.